First year performance of the IceCube neutrino telescope - Achterberg A.; Ackermann M.; Adams J.; Ahrens J.; Andeen K.; Atlee D. W.; Baccus J.; Bahcall J. N.; Bai X.; Baret B.; Bartelt M.; Barwick S. W.; et al. (Astroparticle Physics, 2006)
The first sensors of the IceCube neutrino observatory were deployed at the South Pole during the austral summer of 2004-2005 and have been producing data since February 2005. One string of 60 sensors buried in the ice and a surface array of eight ice Cherenkov tanks took data until December 2005 when deployment of the next set of strings and tanks began. We have analyzed these data, demonstrating that the performance of the system meets or exceeds design requirements. Times are determined across the whole array to a relative precision of better than 3 ns, allowing reconstruction of muon tracks and light bursts in the ice, of air-showers in the surface array and of events seen in coincidence by surface and deep-ice detectors separated by up to 2.5 km. (c) 2006 Elsevier B.V. All rights reserved.